PENERAPAN EVIDANCE BASED NURSING PENGGUNAANVIRGIN COCONUT OIL UNTUK MENGATASI MASALAHINTEGRITAS KULIT PADA ANAK DENGAN RUAM POPOK - Nadia Syaripah Hanum (2022)
Diaper rash is a condition where there is inflammation in the area covered by diapers, including the buttocks, thighs and anal areas. Handling or therapy to treat diaper rash can be given pharmacologically and non-pharmacologically, pharmacological management can be given miconazole ointment, cycloprox or nystatin. Meanwhile, to treat diaper rash non-pharmacologically, one of them can be done by giving coconut oil or Virgin Coconut Oil (VCO) in the diaper rash area. Virgin Coconut Oil is pure coconut oil obtained from processed coconut or copra by fermenting coconut milk without any heating process and the addition of other microbes. Also stated that giving Virgin Coconut Oil twice a day after bathing can reduce the degree of diaper rash that occurs in babies. This innovation intervention analysis was conducted to analyze the effect of using Virgin Coconut Oil (VCO) on the level of skin integrity problems in children with diaper rash at Bhayangkara TK.I Hospital Raden Said Sukanto. This implementation is done by applying Virgin Coconut Oil (VCO) on the skin area of children who have diaper rash 2 times a day, morning and evening for 4 days. The results of the implementation showed a decrease in the degree of diaper rash 1 score, namely moderate degree (score 3) to mild degree (score 2).